2015
DOI: 10.1016/j.desal.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silica on the properties of cellulose acetate/polyethylene glycol membranes for reverse osmosis

Abstract: • 2-stage phase inversion protocol; involving TIPS and controlled evaporation.• Silica is used as an additive to augment permeation performance.• Addition of silica enhanced the fouling resistance remarkably.• Optimum loading of silica particle is required for maximum performance. In this work, a series of cellulose acetate/polyethylene glycol-600 membranes, with varying ratios were prepared by 2-stage phase inversion protocol. The permeation properties were studied by subjecting membranes in indigenously fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Cellulose acetate/polyethylene glycol (CA/PEG) membrane has been observed by Ahmad et al and the result shows that CA/PEG with composition 80/20 has the best performance in salt rejection and flux permeate [7]. The pore number and flux permeate of the cellulose membrane can be increased by the addition of PEG and it is hydrophilic material [8].…”
Section: Introductionmentioning
confidence: 69%
“…Cellulose acetate/polyethylene glycol (CA/PEG) membrane has been observed by Ahmad et al and the result shows that CA/PEG with composition 80/20 has the best performance in salt rejection and flux permeate [7]. The pore number and flux permeate of the cellulose membrane can be increased by the addition of PEG and it is hydrophilic material [8].…”
Section: Introductionmentioning
confidence: 69%
“…According to this model, transport process within the membrane involves three steps: 1) sorption at the surface of the membrane, 2) diffusion into dense membrane under pressure, and 3) desorption. The hydrophilic nature of PEG acts as driving force for sorption of water into the membrane [41].…”
Section: Membrane Performancementioning
confidence: 99%
“…Their study showed that the silica particle significantly influences the permeation performance of composite membrane. Furthermore, their result revealed that the incorporation of SiO 2 content in the casting solution improves the fouling resistance of the membranes …”
Section: Introductionmentioning
confidence: 99%